Structural investigation of crystallized Ge-Ga-Se chalcogenide glasses - Klym, H.; Shpotyuk, O.; Karbovnyk, I.; Calvez, L.; Popov, Anatoli I. (Institute of Physics Publishing, 2019)
Crystallization transformation in the 80GeSe2-20Ga2Se3 chalcogenide glasses caused by annealing at 380 °C during different duration (25, 50, 80 and 100 hours) are studied using X-ray diffraction and atomic force microscopy methods. It is established that GeGa4Se phase of low- and high-temperature modification, Ga2Se3 phase (α- and γ-modification) and GeSe2 phases are crystallized during this process. It is shown that annealing duration over 50 h does not lead to further internal structural crystallization, while annealing for 80 h result in processes of surface crystallization.
H. Klym thanks to the Ministry of Education and Science of Ukraine for support and Dr. P. Demchenko for the assistance in XRD experiments.